Converting policy research into policy decisions: The role of communication and the media - von Grebmer, Klaus (Haworth Press, 2005)
A major challenge in achieving food security in any given developing country is addressing the dichotomy between academic research and policy decision-making. The work that researchers conduct often does not reach policymakers because of inadequate and inappropriate policy communication. The link between research and decision-making systems remains weak. This paper explores the strategies for effective policy communication and provides some suggestions on how policy researchers can reach policymakers and the media to enhance the impact of their findings.